Ilia Chavchavadze and the emergence of Georgian national discourse - Beniamin Mailyan (Banber Arevelagitut'yan Instituti, 2025)
The purpose of this article is to explore the history of the emergence of the discourse of Georgian nationalism and the idea of the Georgian nation. The author offers an alternative view of the reasons for the emergence of Georgian nationalism and identifies the main top-ics of the Georgian national narrative. Ilia Chavchavadze, a poet, a writer, a publicist and a public figure, is considered the spiritual father of the nation in Georgia. He is one of the key figures in the Georgian histor-ical pantheon because he outlined the main ethnic markers of Georgian identity. He and his circle, the group of intellectuals known as Tergdaleulebi, mark the beginning of the history of Georgian nationalism. This makes him an indisputable authority for all those who call themselves Georgian patriots.